An intrinsic association between olfactory identification and spatial memory in humans. Issue 1 (December 2018) - Dahmani, Louisa; Patel, Raihaan; Yang, Yiling; Chakravarty, M.; Fellows, Lesley; Bohbot, Véronique
Abstract It was recently proposed that olfaction evolved to aid navigation. Consistent with this hypothesis, olfactory identification and spatial memory are linked to overlapping brain areas which include the orbitofrontal cortex and hippocampus. However, the relationship between these two processes has never been specifically investigated. Here, we show that olfactory identification covaries with spatial memory in humans. We also found that the cortical thickness of the left medial orbitofrontal cortex, and the volume of the right hippocampus, predict both olfactory identification and spatial memory. Finally, we demonstrate deficits in both olfactory identification and spatial memory in patients with lesions of the medial orbitofrontal cortex. Our findings reveal an intrinsic relationship between olfaction and spatial memory that is supported by a shared reliance on the hippocampus and medial orbitofrontal cortex. This relationship may find its roots in the parallel evolution of the olfactory and hippocampal systems. Olfaction, the sense of smell, may have originally evolved to aid navigation in space, but there is no direct evidence of a link between olfaction and navigation in humans. Here the authors show that olfaction and spatial memory abilities are correlated and rely on similar brain regions in humans.